Theorizing Fundamental Music/Dance Interactions in Salsa. (19th February 2019) - Simpson-Litke, Rebecca; Stover, Chris
Abstract: Communication between music and dance can take many forms. In salsa, this communication begins with and builds upon two simple but crucial criteria: for music, a metric-rhythmic foundation based on clave and other essential performance strata, and for dance, the flow and metric orientation of one of three basic footwork patterns. Most of the rich complexity of music, dance, and their interaction stems from these fundamental gestures. In this article we analyze the basic structures of salsa music and dance, theorize how they interact, and investigate three scenarios where dancers have to make decisions about how to attend to musical features via their footwork orientations.